Stroop interference is a composite phenomenon: Evidence from distinct developmental trajectories of its components. Issue 2 (18th September 2019) - Ferrand, Ludovic; Ducrot, Stéphanie; Chausse, Pierre; Maïonchi‐Pino, Norbert; O'Connor, Richard J.; Parris, Benjamin A.; Perret, Patrick; Riggs, Kevin J.; Augustinova, Maria
Abstract: Only one previous developmental study of Stroop task performance (Schiller, 1966) has controlled for differences in processing speed that exist both within and between age groups. Therefore, the question of whether the early developmental change in the magnitude of Stroop interference actually persists after controlling for processing speed needs further investigation; work that is further motivated by the possibility that any remaining differences would be caused by process(es) other than processing speed. Analysis of data from two experiments revealed that, even after controlling for processing speed using z‐transformed reaction times, early developmental change persists such that the magnitude of overall Stroop interference is larger in 3rd‐ and 5th graders as compared to 1st graders. This pattern indicates that the magnitude of overall Stroop interference peaks after 2 or 3 years of reading practice (Schadler & Thissen, 1981). Furthermore, this peak is shown to be due to distinct components of Stroop interference (resulting from specific conflicts) progressively falling into place. Experiment 2 revealed that the change in the magnitude of Stroop interference specifically results from joint contributions of task, semantic and response conflicts in 3rd‐ and 5th graders as compared to a sole contribution of task conflict in 1st graders. The specific developmental trajectories of different conflicts presented in the present work provide unique evidence for multiple loci of Stroop interference in the processing stream (respectively task, semantic and response conflict) as opposed to a single (i.e. response) locus predicted by historically – favored response competition accounts. Abstract : The present study shows that early developmental change in Stroop interference persists even after controlling for existing differences in processing speed. This change corresponds to an increase such that the 3rd and 5th graders displayed greater Stroop interference compared to 1st graders. This increase results from joint contributions of task, semantic, and response conflicts to Stroop interference in 3rd and 5th graders (vs. task conflict only in 1st graders). The specific developmental trajectories of these different conflicts provide unique evidence for the composite (as opposed to unitary) nature of Stroop interference.